Method for manufacturing aluminum alloy part

By selecting the appropriate aluminum alloy composition in the additive manufacturing method, combining Zr, Hf, Er and Cr, V, Ti, Mn and other elements, the problem that aluminum alloy parts in the prior art is difficult to achieve high mechanical properties and conductivity without heat treatment, and excellent processing performance and mechanical properties are achieved in the LPBF method.

CN119731357APending Publication Date: 2025-03-28C TEC CONSTELLIUM TECH CENT
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380060238.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing additive manufacturing technology is difficult to obtain aluminum alloy parts with high mechanical properties and conductivity without heat treatment, and the mechanical characteristics of pure aluminum are low, which limits its use.

Method used

By appropriately selecting the additive elements, an aluminum alloy composition for an additive manufacturing method (particularly LPBF) is determined, which comprises at least one alloy element selected from Zr, Hf and Er, and at least one alloy element selected from Cr, V, Ti and Mn, combined with other alloy elements, to form an aluminum alloy, ensuring good conductivity and low hardness in the original state of manufacture, and maximizing hardness and mechanical properties after heat treatment.

Benefits of technology

It achieves excellent parts processing performance and mechanical properties in use in additive manufacturing methods, while avoiding part deformation caused by heat treatment, and meeting the needs of high conductivity and high mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731357A_ABST
    Figure CN119731357A_ABST
Patent Text Reader

Abstract

A method of manufacturing a part (20), comprising forming successive layers of metal (201... 20n) stacked on top of each other, each layer being formed by depositing a filler metal (15, 25), supplying energy to the filler metal, melting the filler metal, and forming said layer by solidification, characterized in that the filler metal (15, 25) is formed on top of the metal layer (201... 20n), and the metal layer (201... 20n) is formed on top of the metal layer (201... 20n). 25) is an aluminum alloy comprising the following alloying elements (in% by weight):-at least one alloying element selected from the group consisting of Zr, Hf and Er, the respective and total weight fractions thereof being greater than or equal to 0.30; -at least one alloying element selected from the group consisting of Cr, V, Ti and Mn in respective and total weight fractions greater than 0.50%; fe, the mass fraction of which is 0.10 to 2.50%; -optionally Co, La, Ce, a rare earth metal mixture, W, Ta, Mo, Nb, Ni, Cu, Ag, Si, Sc, Mg, Zn, Li, Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In, Sn and impurities; and the balance of aluminum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical field of the present invention relates to a method for manufacturing a part made of aluminum alloy using additive manufacturing technology. Background Art

[0002] Additive manufacturing techniques have been developed since the 80s. They consist of forming parts by adding material, as opposed to machining techniques that aim to remove material. Previously limited to prototyping, additive manufacturing can now be used to manufacture industrial products, including metal parts, in a mass-produced manner.

[0003] The term "additive manufacturing" is defined according to the French standard XP E67-001 as "a collection of methods that allow the manufacture of physical objects layer by layer, based on digital objects, by adding material". Additive manufacturing is also defined in the standard ASM F2792 (January 2012). Different additive manufacturing methods are also defined and described in the standard ISO / ASTM 17296-1. The preparation of aluminum parts with low porosity by means of additive manufacturing has been described in document WO2015006447. Typically, successive layers are applied by applying a so-called filler material and then melting or sintering the filler material using an energy source of the laser beam, electron beam, plasma torch or arc type. Whatever the additive manufacturing method applied, the thickness of each added layer is tens or hundreds of micrometers.

[0004] Other additive manufacturing methods may also be used. For example, and without limitation, melting or sintering of filler materials in powder form may be mentioned. This may include laser melting or sintering. Patent application US20170016096 describes a method for manufacturing parts by locally melting powders by exposing the powders to an energy beam, such as an electron beam or a laser beam, which is also named LPBF in English by the acronym, meaning "laser powder bed melting" or "electron beam melting".

[0005] The mechanical properties of aluminum parts obtained by additive manufacturing depend on the alloy forming the filler metal, and more specifically on its composition, as well as on the heat treatment applied after the implementation of additive manufacturing.

[0006] The Applicant has identified an alloy composition which, when used in an additive manufacturing method, makes it possible to obtain parts with excellent mechanical properties without having to carry out heat treatments such as solution heat treatment and quenching.

[0007] For aluminum alloys, pure aluminum generally obtains the maximum electrical conductivity or thermal conductivity. However, the mechanical properties of pure aluminum are low, which limits its field of use. In order to improve the mechanical strength of pure aluminum, the content of additive elements can be increased. Conversely, in order to improve the electrical conductivity of aluminum alloys, the content of additive elements other than aluminum can be limited. Therefore, changes in the total content of additive elements affect the conductivity and mechanical strength of aluminum alloys in a contradictory way. In addition, it is difficult to design an aluminum alloy that has sufficient thermal conductivity in the original state of manufacturing and sufficient mechanical strength after heat treatment.

[0008] According to one variant of the invention, the Applicant has determined, by suitable selection of the additive elements, compositions of aluminium alloys intended for additive manufacturing processes, in particular LPBF, which allow very good part processing properties to be obtained in the LPBF process and excellent mechanical properties of the parts in use. Good part processing properties in the LPBF process are obtained by combining a sufficiently low hardness level in the original state of manufacture (e.g. a Knoop hardness HK0.05 in the original state of manufacture of less than 140, preferably less than 130, preferably less than 120) and a sufficiently high thermal or electrical conductivity (e.g. an electrical conductivity in the original state of manufacture of greater than 6MS / m, preferably greater than 7MS / m, preferably greater than 8MS / m). This combination of hardness and conductivity makes it possible to limit the residual stress levels of the parts in the original state of manufacture, significantly limiting the risks of cracking, delamination or deformation, and thus significantly improving the part processing properties in the LPBF process. Excellent mechanical properties of the part in use are obtained by maximizing the hardness of the part after post-manufacturing heat treatment (e.g., Knoop hardness HK0.05 above 70, preferably above 80, preferably above 90, preferably above 100, preferably above 114).

[0009] Pure aluminum powder can be used as a reducing agent in solid propellant fuel for aerospace thrusters. Therefore, in some countries, aluminum powders with more than 97% aluminum are often considered dual-use goods (DUG) requiring an export license. This classification represents a constraint that may hinder the commercialization of some aluminum powders with more than 97% aluminum intended for use in additive manufacturing methods (such as LPBF). Therefore, it is more advantageous to develop solutions with less than 97% aluminum (i.e. more than 3% total amount of added elements).

[0010] According to another variant of the invention, the Applicant has determined, by suitable selection of the additive elements, aluminium alloy compositions intended for additive manufacturing methods (particularly LPBF), which compositions contain a total amount of additive elements exceeding 3% and which allow good processing properties of the parts in the LPBF method while maximizing the mechanical properties of the parts in use. Summary of the invention

[0011] A first object of the invention is a method for manufacturing a part, comprising forming successive metal layers superposed on one another, each layer being formed by depositing a filler metal which melts after energy input and forms said layer when solidifying, said method being characterized in that said filler metal is an aluminum alloy containing the following alloying elements (in percentages by weight):

[0012] - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%;

[0013] - at least one alloying element selected from Cr, V, Ti and Mn, the mass fraction of V, Ti and Mn being greater than 0.50% each and in total, preferably greater than 0.50 to 6.00%, preferably 1.00 to 6.00%, preferably 1.00 to 5.00%, more preferably 1.00 to 4.00%, even more preferably 1.00 to 3.00%; the mass fraction of Cr being greater than 0.50 to 3.00%;

[0014] - optionally at least one alloying element selected from Co, La, Ce, mischmétal, W, Ta, Mo and Nb, the mass fractions of which are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and the mass fractions of which are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and the mass fractions of which are in total less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%;

[0015] - Fe, whose mass fraction is 0.10 to 2.50%, preferably 0.15 to 2.50%, preferably 0.20 to 2.50%, more preferably 0.30 to 2.50%, even more preferably 0.50 to 2.50%, even more preferably 0.75 to 2.25%;

[0016] - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0017] - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%;

[0018] - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%,

[0019] Preferably less than 0.20%;

[0020] - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%;

[0021] - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%;

[0022] - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%;

[0023] - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%;

[0024] - optionally at least one element chosen from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, the mass fractions of which are each less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%,

[0025] Preferably less than or equal to 0.30%;

[0026] - Impurities: <0.05% individually and preferably <0.15% in total;

[0027] The rest is aluminum.

[0028] In particular, each layer may describe a pattern defined by a digital model.

[0029] According to one embodiment, the filler metal is in the form of a powder, which is exposed to a light beam or charged particle beam, causing local melting and then solidification to form a solid layer. According to another embodiment, the filler metal originates from a filler wire, which is exposed to a heat source, such as an electric arc, causing local melting and then solidification to form a solid layer.

[0030] A second object of the present invention is a metal part obtained by the method according to the first or second object of the present invention.

[0031] A third object of the invention is a filler material, in particular a filler wire or powder, intended for use as a filler material in an additive manufacturing method, said filler material being characterized in that it consists of an aluminum alloy containing the following alloying elements (in weight %):

[0032] - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%;

[0033] - at least one alloying element selected from Cr, V, Ti and Mn, the mass fraction of V, Ti and Mn being greater than 0.50% each and in total, preferably greater than 0.50 to 6.00%, preferably 1.00 to 6.00%, preferably 1.00 to 5.00%, more preferably 1.00 to 4.00%, even more preferably 1.00 to 3.00%; the mass fraction of Cr being greater than 0.50 to 3.00%;

[0034] - optionally at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and Nb, the mass fraction of which is each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and the mass fraction of which is each less than

[0035] 5.00%, preferably less than 4.00%, preferably less than 3.00%; and the total mass fraction thereof

[0036] Less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%; - Fe, the mass fraction of which is 0.10 to 2.50%, preferably 0.15 to 2.50%, preferably 0.20

[0037] 0.50 to 2.50%, more preferably 0.30 to 2.50%, even more preferably 0.50 to 2.50%, even more preferably 0.50 to 2.50%,

[0038] to more preferably 0.75 to 2.25%;

[0039] - optionally Ni, with a mass fraction of less than 3.00%, preferably less than 2.00%, preferably less than

[0040] 1.00%, preferably less than 0.50%;

[0041] - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are each and the total

[0042] 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably

[0043] Select 0.10 to 1.00%, preferably 0.10 to 0.70%;

[0044] - optionally Si, with a mass fraction of less than 3.00%, preferably less than 2.00%, preferably less than

[0045] 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, preferably less than 0.20%;

[0046] - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than

[0047] 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%;

[0048] - optionally Mg, with a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than

[0049] 0.50%, more preferably less than 0.30%;

[0050] - optionally Zn, with a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than

[0051] 0.50%, more preferably less than 0.30%;

[0052] - optionally Li, with a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than

[0053] 0.50%, more preferably less than 0.30%;

[0054] - optionally at least one element chosen from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, the mass fractions of which are each less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%;

[0055] - Impurities: <0.05% each and <0.15% in total;

[0056] The rest is aluminum.

[0057] The aluminum alloy forming the filler material may have the characteristics described in relation to the first aspect of the present invention.

[0058] The filler material may be in the form of a powder. The powder may be such that at least 80% of the particles making up the powder have an average size in the range of 5 to 200 μm, preferably 5 to 150 μm, preferably 5 to 25 μm, or 20 to 60 μm or 20 to 80 μm or 20 to 90 μm or 20 to 100 μm or 20 to 110 μm or 20 to 120 μm.

[0059] In case the filler material is in the form of a metal wire, the diameter of the metal wire may in particular be 0.5 mm to 3 mm, preferably 0.5 mm to 2 mm, more preferably 1 mm to 2 mm.

[0060] A fourth object of the invention is the use of a powder or filler wire as described above and in the remainder of this description for a manufacturing method selected from the group consisting of electron beam melting, cold spray consolidation, laser melting deposition, additive friction stir, field assisted sintering or inertial rotation friction welding, preferably cold spray consolidation.

[0061] Other advantages and features will emerge more clearly from the following description of specific embodiments of the invention, which are provided as non-limiting examples and are shown in the figures listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] [ Figure 1 ] Figure 1 is a schematic diagram illustrating the LPBF type additive manufacturing method.

[0063] [ Figure 2 ] Figure 2 is a schematic diagram illustrating a WAAM type additive manufacturing method.

[0064] [ Figure 3 ] Figure 3 is a schematic diagram of a plaquette after laser reflow according to an embodiment.

[0065] [ Figure 4 ] Figure 4 It is a schematic diagram of the Knoop hardness measurement test. DETAILED DESCRIPTION

[0066] Unless otherwise stated, in this manual:

[0067] - The naming of aluminum alloys complies with the nomenclature of The Aluminum Association;

[0068] - The content of chemical elements is reported in % and represents mass fraction. The symbol x%-y% means greater than or equal to x% and less than or equal to y%.

[0069] Impurities are understood to be chemical elements that are not intentionally present in the alloy.

[0070] Figure 1 The operation of an additive manufacturing method of the selective laser melting type (laser powder bed melting or LPBF) is represented diagrammatically. A filler metal 15 is arranged in the form of a powder on a support 10. An energy source, in this case a laser source 11, emits a laser beam 12. The laser source is coupled to the filler material via an optical system 13, the movement of which is determined according to a numerical model M. The laser beam 12 propagates along a propagation axis Z and moves according to a plane XY, describing a pattern according to the numerical model M. For example, the plane is perpendicular to the propagation axis Z. The interaction of the laser beam 12 with the powder 15 results in selective melting of the powder 15, which then solidifies, thereby forming layers 201 ... 20 n When one layer has been formed, it is covered with powder 15 of filler metal and another layer is formed superimposed on the previously prepared layer. For example, the thickness of the layer may be 10 to 250 μm, such as 30 μm, 60 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.

[0071] The increase in layer thickness may be beneficial for increasing productivity during printing and limiting the susceptibility to thermal cracking associated with residual stresses during part manufacturing and / or post-manufacturing heat treatment. The increase in layer thickness may be accompanied by adaptive changes in laser power, vector deviation (the distance between two consecutive laser passes) and laser scanning speed to ensure complete melting of each powder layer under optimal conditions. For example, the layer thickness may be 60 to 250 μm, preferably 80 to 200 μm, preferably 90 to 180 μm, preferably 100 to 180 μm, preferably 110 to 170 μm, preferably 120 to 160 μm.

[0072] For aluminum alloys, the support 10 or the tray can be heated to a preheating temperature T of up to 500°C. Typically, the machines currently available on the market can heat the tray up to 200°C. For example, the heating temperature of the tray (= preheating temperature T) can be about 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C. In general, heating the tray makes it possible to reduce the humidity in the powder bed and at the same time reduce the residual stresses on the part during manufacturing. The humidity level at the powder bed seems to have a direct impact on the porosity of the final part. In fact, it seems that the higher the humidity of the powder, the higher the porosity of the final part. It should be noted that heating the tray is one of the existing possible options for implementing thermal additive manufacturing. However, the present invention cannot be limited to the use of only this heating method. All other heating methods that allow the implementation of this preheating step can be used in the context of the present invention for heating and controlling the temperature, such as infrared lamps. Therefore, the method according to the present invention can be carried out at a preheating temperature T of up to 500°C.

[0073] For some compositions, the inventors have noticed that when the preheating temperature T is lower than or equal to 160°C and higher than or equal to 25°C, the parts have better resistance to thermal cracking associated with residual stresses. Preferably, the preheating tray and therefore the preheating of the powder bed can be carried out at a preheating temperature T lower than or equal to 140°C, or, better yet, lower than or equal to 130°C. The preheating temperature T is higher than room temperature. The preferred range of the preheating temperature T is: 25°C≤T≤160°C, preferably 30°C≤T≤150°C, preferably 50°C≤T≤150°C, preferably 50°C≤T≤140°C, preferably 60°C≤T≤140°C, preferably 70°C≤T≤135°C, preferably 80°C≤T≤130°C.

[0074] According to an alternative, the preheating temperature T corresponds to conditions that enable effective relaxation to be obtained. The preheating temperature range T can then be 300° C. to 500° C., preferably 300 to 400° C., preferably 300 to 350° C. It is believed that in this preheating temperature range T, the manufacturing conditions of the part produce less residual stress. According to this alternative, post-manufacturing heat treatment relaxation is also relevant, as described later in this specification.

[0075] The powder according to the invention may have at least one of the following characteristics:

[0076] - an average particle size of 5 to 200 μm, preferably 5 to 150 μm, preferably 5 to 25 μm, or 20 to 60 μm, or 20 to 80 μm, or 20 to 90 μm, or 20 to 100

[0077] The data values ​​mean that at least 80% of the particles have an average particle size within the specified range.

[0078] - Spherical shape. For example, the sphericity of a powder can be determined using a particle morphology analyzer.

[0079] - Good castability. For example, the castability of the powder can be determined according to standard ASTM B213 or standard ISO 4490:2018. According to standard ISO 4490:2018, the flow time is preferably shorter than 50.

[0080] - low porosity, preferably 0 to 5% by volume, more preferably 0 to 2% by volume, even more preferably 0 to 1% by volume. The porosity can be determined in particular by analyzing images of optical micrographs or by the helium pycnometer method (see standard ASTM B923).

[0081] The absence or presence of a small amount (less than 10% by volume, preferably less than 5% by volume) of small particles (1 to 20% of the average particle size of the powder), so-called satellite particles, which adhere to the larger particles.

[0082] Implementation of this approach allows high throughput manufacturing of parts, reaching and even exceeding 200 cm by laser. 3 / h.

[0083] Furthermore, the Applicant has observed that the application of post-manufacturing heat treatments, such as quenching, may cause deformations of the parts due to drastic temperature changes. Usually, due to their large dimensions, their deformations are even more significant. However, the advantage of the additive manufacturing method is precisely to obtain parts whose shape is permanent or quasi-permanent after manufacturing. Therefore, the occurrence of significant deformations of the parts due to post-manufacturing heat treatments should be avoided. "Quasi-permanent" should be understood as the possibility of finishing the parts after their manufacture: the parts manufactured by additive manufacturing are extended according to their final shape within the finishing allowance.

[0084] Having noted the above, the Applicant has searched for an alloy composition for forming the filler material that allows obtaining acceptable mechanical properties and electrical or thermal conductivity without having to apply a heat treatment after the layer formation (i.e. after the final part has been formed), which heat treatment could cause deformations. In particular, the aim is to avoid heat treatments involving sudden changes in temperature. The invention thus allows obtaining, by additive manufacturing, parts that are satisfactory in terms of mechanical properties, in particular in terms of yield strength, and in terms of electrical or thermal conductivity. The filler material can be in the form of a wire or a powder, depending on the type of additive manufacturing method chosen.

[0085] The following elements can be used in aluminum alloys.

[0086] Zr, Hf and / or Er:

[0087] According to the present invention, at least one alloying element selected from Zr, Hf and Er is present in the aluminum alloy, and its mass fraction is greater than or equal to 0.30% each and in total, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%. Preferably, the mass fraction of at least one alloying element selected from Zr, Hf and Er is greater than or equal to 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65% or 0.70% each and in total. Preferably, the mass fraction of at least one alloying element selected from Zr, Hf and Er is individually and in total less than or equal to 2.50%, 2.40%, 2.30%, 2.20%, 2.10%, 2.00%, 1.90%, 1.80%, 1.70%, 1.60%, 1.50%, 1.40% or 1.30%.

[0088] These elements have high solid solubility in the original state of manufacture. Therefore, their addition can significantly reduce the conductivity in the original state. However, adding a post-manufacturing heat treatment, for example at a temperature of 300 to 450°C for 0.5 to 10 hours, can allow to significantly reduce their content in solid solution by forming Al3X type hardening dispersed phases (X = Zr or Hf or Er). During the heat treatment, the formation of these dispersed phases can allow to increase both hardness and conductivity relative to the original state.

[0089] These elements may also allow for control of the grain structure during laser melting by promoting the appearance of equiaxed grains.

[0090] Furthermore, the presence of at least one alloying element selected from Zr, Hf and Er in the alloy can give the alloy good processing properties, a term corresponding to the English name "processability", which refers to the ability of the alloy to be formed by additive manufacturing methods. This can be manifested at the level of the parts manufactured by additive manufacturing as a quasi-absence of crack-type defects, as well as a low porosity.

[0091] Cr, V, Ti and / or Mn:

[0092] According to the present invention, at least one alloying element selected from Cr, V, Ti and Mn is present in the aluminum alloy, and the mass fractions of V, Ti and Mn are each greater than 0.50%, preferably greater than 0.50 to 6.00%, preferably 1.00 to 6.00%, more preferably 1.00 to 5.00%, even more preferably 1.00 to 4.00%, even more preferably 1.00 to 3.00%; the mass fraction of Cr is greater than 0.50 to 3.00%. Preferably, the mass fractions of at least one alloying element selected from Cr, V, Ti and Mn are each greater than 0.50%, or greater than or equal to 0.60%, 0.70%, 0.80%, 0.90% or 1.00%. Preferably, the mass fraction of at least one alloying element selected from Cr, V, Ti and Mn is individually and in total less than or equal to 6.00%, 5.50%, 5.00%, 4.50%, 4.00%, 3.50%, 3.00%, 2.50%, 2.00%, 1.50% or 1.00%.

[0093] These elements may allow to increase the mechanical strength of the alloy through solid solutions and / or dispersed phases that may be formed during the manufacture of the part or during post-manufacturing heat treatments. However, these elements have a high solubility in aluminum and have a negative impact on conductivity. The addition of these elements is beneficial for alloys whose target applications do not require specific properties in terms of electrical or thermal conductivity, but require high mechanical strength, such as structural parts, hydraulic blocks, etc.

[0094] Co, La, Ce, mischmetal, W, Ta, Mo and / or Nb:

[0095] According to the present invention, at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and / or Nb may be present in the aluminum alloy, and its mass fraction is at least 0.10%, preferably at least 0.25%, more preferably at least 0.50% each and in total; and its mass fraction is less than 5.00%, preferably less than 4.00%, preferably less than 3.00% each; and its mass fraction is less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%. Preferably, the mass fraction of at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and Nb is greater than or equal to 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45% or 0.50% each and in total. Preferably, the mass fraction of at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and Nb is less than 5.00%, 4.50%, 4.00%, 3.50% or 3.00% respectively. Preferably, the mass fraction of at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and Nb is less than 7.00%, 6.50%, 6.00%, 5.50%, 5.00%, 4.50% or 4.00% in total.

[0096] These elements can allow for increased mechanical strength of the alloy through solid solution and / or through dispersed phases that can form during part fabrication or during post-fabrication heat treatment. These elements have very low solid solubility in aluminum. Adding these elements can harden the alloy without significantly negatively affecting conductivity.

[0097] Preferably, the aluminum alloy contains at least one alloying element selected from the group consisting of Co, La, Ce, mischmetal, W, Ta, Mo and Nb.

[0098] Fe:

[0099] According to the present invention, the element Fe is present in the aluminum alloy in a mass fraction of 0.10 to 2.50%, preferably 0.15 to 2.50%, preferably 0.20 to 2.50%, more preferably 0.20 to 2.50%, even more preferably 0.30 to 2.50%, even more preferably 0.50 to 2.50%, even more preferably 0.75 to 2.25%. Preferably, the mass fraction of Fe is greater than or equal to 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70% or 0.75%. Preferably, the mass fraction of Fe is less than or equal to 2.50%, 2.40%, 2.30%, 2.20% or 2.25%.

[0100] This element can allow for an increase in the mechanical strength of the alloy through solid solution and / or through dispersed phases that can form during part fabrication or during post-fabrication heat treatment. This element has a low solid solubility in aluminum. The addition of this element can harden the alloy without significantly negatively affecting conductivity.

[0101] Ni:

[0102] According to the present invention, the element Ni may be present in the aluminum alloy in an amount of less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%. Preferably, the mass fraction of Ni is greater than 500 ppm, preferably greater than 0.10%, preferably greater than 0.15%, preferably greater than 0.20%, preferably greater than 0.30%, preferably greater than 0.40%.

[0103] This element can allow for an increase in the mechanical strength of the alloy through solid solution and / or through dispersed phases that can form during part fabrication or during post-fabrication heat treatment. This element has a very low solid solubility in aluminum. The addition of this element can harden the alloy without significantly affecting conductivity.

[0104] Cu and / or Ag:

[0105] According to the invention, the elements Cu and / or Ag may be present in the aluminum alloy in a mass fraction of 0.10 to 3.00% individually and in total, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%.

[0106] These elements may allow for an increase in the mechanical strength of the alloy through solid solution and / or hardening precipitates that may be formed during part fabrication or during post-fabrication heat treatment.

[0107] Si:

[0108] According to the present invention, the element Si may be present in the aluminum alloy, and its mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, preferably less than 0.20%. Preferably, the mass fraction of Si is greater than 500ppm, preferably greater than 0.10%, preferably greater than 0.15%.

[0109] Addition of Si in the presence of Zr results in the formation of a coarse AlZrSi phase which limits the hardening ability of Zr after heat treatment.

[0110] Sc:

[0111] According to the present invention, the element Sc may be present in the aluminum alloy, and its mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%. Preferably, the mass fraction of Sc is greater than 500ppm, preferably greater than 0.10%, preferably greater than 0.15%, preferably greater than 0.20%.

[0112] This element may have the same technical effect as the elements Zr, Hf and Er. On the other hand, according to a variant of the invention, the inventors have noticed that a good compromise between mechanical properties and conductivity can also be obtained, preferably after heat treatment, by replacing at least part of the group of elements Co, La, Ce, mischmetal, W, Ta, Mo and / or Nb with Sc in mass fractions as described above.

[0113] Mg, Zn and / or Li:

[0114] According to the present invention, the elements Mg, Zn and / or Li may be present in the aluminum alloy, and their mass fractions are each less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, and more preferably less than 0.30%. Preferably, the mass fractions of Mg, Zn and / or Li are each greater than 500 ppm, preferably greater than 0.10%, and preferably greater than 0.15%.

[0115] These elements can allow to improve the mechanical strength of the alloy through solid solution. However, these elements are sensitive to evaporation during laser melting, which may lead to smoke formation and instability of the molten pool. Excessive addition of these elements can significantly reduce electrical conductivity. Therefore, according to one embodiment, the addition of these elements should preferably be avoided.

[0116] Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and / or Sn:

[0117] According to the present invention, at least one element selected from the group consisting of Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn may be present in the aluminum alloy, the mass fraction of each of which is less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and the total is less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%. Preferably, the mass fractions of Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn are each and the total is greater than 100 ppm, preferably greater than 300 ppm, preferably greater than 500 ppm.

[0118] These elements may allow to increase the mechanical strength of the alloy through solid solution and / or through dispersed phases that may be formed during part manufacturing or during post-manufacturing heat treatment. However, excessive addition of these elements may reduce the conductivity of the alloy, and for this reason, according to one embodiment, their addition is preferably done in a mass fraction of less than 700 ppm each.

[0119] It should be noted that, preferably, the alloy according to the present invention is not an AA6xxx alloy, since there are no simultaneous additions of Si and Mg greater than 0.2%.

[0120] The method may include applying at least one heat treatment after forming the layers, i.e. after forming the final part. Such treatment is also referred to as post-fabrication or post-processing heat treatment. Post-fabrication heat treatment may be or include tempering or annealing. It may also include solution heat treatment and quenching, although these are preferably avoided. It may also include hot isostatic pressing.

[0121] According to a first variant, a post-manufacturing heat treatment may be carried out in order to favour the mechanical properties:

[0122] - at a temperature T′ higher than 400° C., in which case the duration of the post-production heat treatment is from 0.1 h to 50 h, preferably from 0.1 h to 10 h;

[0123] - or at a temperature T' of 300 to 400°C, in which case the duration of the post-production heat treatment is 0.1 h to 200 h.

[0124] According to a second variant, in order to favour thermal or electrical conductivity, a post-manufacturing heat treatment may be carried out at a temperature T′ higher than or equal to 350° C. or 400° C., for a duration ranging from 0.1 h to 200 h, in order to obtain an optimum thermal or electrical conductivity.

[0125] According to another variant, a two-step post-manufacturing heat treatment can allow the electrical conductivity to be maximized. These treatments consist of a first step at a temperature T′1 above 450° C. for a duration of 0.1 h to 100 h, followed by a second step at a temperature T′2 between 300° C. and 450° C. for a duration of 0.1 h to 200 h.

[0126] According to another variant, a two-step post-manufacturing heat treatment can maximize the electrical conductivity and / or hardness. These treatments consist of a first step at a temperature T′1 below 380° C. for a duration of 0.1 h to 200 h, followed by a second step at a temperature T′2 between 380° C. and 450° C. for a duration of 0.1 h to 200 h.

[0127] According to another variant, a three-step post-manufacturing heat treatment can maximize the electrical conductivity and / or hardness. These treatments consist of a first step at a temperature T′1 of 250°C to 450°C for 0.1h to 200h, followed by a second step at a temperature T′2 above 450°C for 0.1h to 100h, followed by a third step at a temperature T′3 of 250°C to 450°C for 0.1h to 200h.

[0128] Multi-step processing with more than 3 steps can also be considered.

[0129] According to one embodiment, the method may include hot isostatic pressing (HIP). In particular, the HIP treatment may allow for improved tensile properties and fatigue properties. Hot isostatic pressing may be performed before, after or instead of post-manufacturing heat treatment. Advantageously, hot isostatic pressing is performed at a temperature of 250° C. to 500° C., preferably 300° C. to 450° C., at a pressure of 500 to 3,000 bar, and for a duration of 0.5 to 100 hours.

[0130] According to an advantageous embodiment, the method does not comprise any quenching after forming the layer, ie after forming the final part, or after a post-manufacturing heat treatment. Thus, preferably, the method does not comprise a step of quenching after the solution heat treatment.

[0131] By means of a post-fabrication heat treatment, the fabrication being carried out by an additive manufacturing method, it is possible to create relaxation conditions, allowing the elimination of residual stresses and the precipitation of hardened phases. We also discuss thermal relaxation. The inventors have observed that the preferred setpoint temperature T' for the post-fabrication heat treatment is between 300°C and 500°C.

[0132] In particular, possible heat treatments and / or hot isostatic pressing allow to improve the hardness or yield strength and the electrical conductivity of the product obtained. However, it should be noted that generally the higher the temperature, the greater the improvement in conductivity (electrical or thermal), but at the expense of mechanical strength.

[0133] According to one embodiment, in addition to the temperature T' of the post-manufacturing heat treatment, the temperature rise at the start of the post-manufacturing heat treatment is preferably as fast as possible. For example, during the temperature rise, the temperature rise rate ΔT' (commonly referred to by those skilled in the art as the "heating rate" in °C per minute or °C per second) is preferably higher than 5 °C per minute or higher than 10 °C per minute, or more preferably higher than 20 °C per minute, more advantageously higher than 40 °C per minute, and more advantageously higher than 100 °C per minute. "Heat rise" should be understood as the temperature rise to which the part is subjected during the post-manufacturing heat treatment. It seems that the best way is that the temperature rise is instantaneous, that is, the manufactured part is subjected to the post-manufacturing heat treatment setpoint temperature T' from the beginning of the post-manufacturing heat treatment. Instantaneous temperature rise can be obtained by placing the manufactured part in a hot furnace that has reached the setpoint temperature T', or by a rapid heating method of fluidized bed or molten salt bath type. The temperature rise can also be ensured by induction heating.

[0134] For the same external heating of the part, the variation of the temperature inside the part depends in particular on the heating medium (liquid or air or inert gas) and on the shape of the part. In particular, the temperature may be different over the thickness of the part or on the surface. This is why the heating mentioned above corresponds to the temperature outside the part. The combination of the preheating temperature T, the post-manufacturing heat treatment T' and the heating rate ΔT' during the heating of the post-manufacturing heat treatment within the above-mentioned numerical ranges allows to obtain parts with good resistance to thermal cracking.

[0135] According to another embodiment (suitable for structural hardening alloys), the formed part can be solution heat treated, followed by quenching and tempering and / or hot isostatic pressing. In this case, hot isostatic pressing can advantageously replace solution heat treatment.

[0136] However, the method according to the invention is advantageous because it preferably does not require a treatment comprising a solution heat treatment followed by a quench. In certain cases, a solution heat treatment can adversely affect the mechanical strength by contributing to the enlargement of dispersed phases or fine intermetallic phases. Preferably, the method according to the invention does not comprise a solution heat treatment and / or a quench, which is performed after the formation of the layer, i.e. after the formation of the final part, or after a post-manufacturing heat treatment.

[0137] Preferably, the method according to the present invention provides a part 20 having:

[0138] - in the original state of manufacture, the electrical conductivity is higher than 6 MS / m, preferably higher than 7 MS / m, preferably higher than 8 MS / m; and

[0139] - In the original state of manufacture, the Knoop hardness HK0.05 is lower than 140, preferably lower than 130,

[0140] Preferably less than 120; and

[0141] After post-treatment at 400° C. for 4 hours, the Knoop hardness HK0.05 is higher than 70, preferably higher than 80, preferably higher than 90, preferably higher than 100, preferably higher than 114.

[0142] According to one embodiment, optionally, the method according to the invention further comprises a mechanical machining treatment, and / or a chemical, electrochemical or mechanical surface treatment, and / or a vibration finishing (tribofinition). In particular, these treatments can be performed to reduce roughness and / or to increase corrosion resistance and / or to increase resistance to fatigue crack initiation.

[0143] Optionally, mechanical deformation of the part may be performed, for example after additive manufacturing and / or before heat treatment.

[0144] Although described in relation to an LPBF type additive manufacturing method, the method may also be applied to other WAAM (Wire plus Arc Additive Manufacturing) type additive manufacturing methods mentioned in relation to the prior art. Figure 2 Such an alternative is shown. An energy source 31, in this case a torch, forms an electric arc 32. In this arrangement, the torch 31 is held by a welding robot 33. The part 20 to be manufactured is arranged on a support 10. In this embodiment, the part to be manufactured is a wall extending along a transverse axis Z perpendicular to the plane XY defined by the support 10. Under the action of the electric arc 12, a filler wire 35 melts to form a weld. The welding robot is controlled by a digital model M. It is moved to form the different layers 201 ... 20 n , the layers are stacked one on top of another to form a wall 20, each layer corresponding to a weld. n It extends in the plane XY according to the pattern defined by the digital model M.

[0145] Preferably, the diameter of the filler wire is less than 3 mm. It may be 0.5 mm to 3 mm, and preferably 0.5 mm to 2 mm, or 1 mm to 2 mm. For example, it is equal to 1.2 mm.

[0146] In addition, other methods may be considered, such as but not limited to:

[0147] -Selective Laser Sintering;

[0148] -Direct Metal Laser Sintering;

[0149] -Selective Heat Sintering;

[0150] - Electron Beam Melting;

[0151] -Laser Melting Deposition;

[0152] - Direct Energy Deposition;

[0153] - Direct Metal Deposition;

[0154] -Direct Laser Deposition;

[0155] -Laser Deposition Technology;

[0156] -Laser Engineering Net Shaping;

[0157] -Laser Cladding Technology;

[0158] -Laser Freedom Manufacturing Technology;

[0159] -Laser Metal Deposition;

[0160] -Cold Spray Consolidation;

[0161] -Additive Friction Stir;

[0162] - Field Assisted Sintering Technology or spark plasma sintering; or

[0163] -Inertia Rotary Friction Welding.

[0164] The solution according to the invention is particularly suitable for cold spraying methods (so-called "cold spray"), in particular because the powder has a low hardness, which facilitates deposition. The component can then be hardened by hardening annealing (thermal post-treatment).

[0165] The solution according to the invention is particularly suitable for applications in the electrical, electronic and heat exchanger industries.

[0166] The present invention will be disclosed in detail in the examples hereinafter, which are given for non-limiting illustrative purposes.

[0167] Experimental Examples

[0168] Example 1

[0169] The experimental alloys were cast in copper moulds using an Induthem VC 650V machine to obtain ingots with a height of 130 mm, a width of 95 mm and a thickness of 5 mm.

[0170] The alloys as described in Table 1 below were tested by a rapid prototyping method. Samples were machined from the ingots obtained above for laser scanning of the surface, in the form of sheets with dimensions of 60×22×3 mm. The sheets were placed in an LPBF machine and the surface was scanned with a laser following the same representative scanning strategy and process conditions as for the LPBF method. In fact, it has been found that by this method, the ability of the alloys to the LPBF method, in particular the hot cracking sensitivity, the hardness in the original state and after heat treatment, the electrical conductivity in the original state and after heat treatment, can be evaluated.

[0171] Under the laser beam, the metal melts into a molten pool with a thickness of about 500 μm. After the laser passes, the metal cools rapidly, just like in the LPBF method. After the laser scan, a thin layer of about 500 μm thick on the surface melts and then solidifies. Due to the appropriate selection of the scanning parameters, the properties of this layer of metal are close to those of the metal in the core of the part manufactured by LPBF. The surface of different samples was laser scanned by a 350 selective laser powder bed fusion (LPBF) machine. The laser source power was 400W, the vector deviation was 60μm, the scanning speed was 500mm / s, and the beam diameter was 65μm.

[0172] On each sheet, two 5 mm x 35 mm rectangular surfaces were melted for hardness measurement, and one 15 mm x 18 mm rectangular surface was melted for conductivity measurement.

[0173] Figure 3An example of a sheet after laser reflow is shown. Mark 1 corresponds to the two remelted rectangular surfaces used for hardness measurements, mark 2 corresponds to the remelted rectangular surface used for conductivity measurements, and mark 3 corresponds to the non-remelted surface of the initial sheet.

[0174] After each test, some samples were subjected to a thermal post-treatment of the annealing type at 400°C for 1, 4 or 7 hours.

[0175] Knoop hardness measurement

[0176] Hardness is the main property of an alloy. In fact, if the hardness of the layer remelted by scanning the surface with a laser is high, the part made of the same alloy will have a high yield strength.

[0177] To evaluate the hardness of the remelted layer, the sheets obtained above were cut in a plane perpendicular to the direction of the laser path and subsequently polished. After polishing, the hardness of the remelted layer was measured. The hardness measurement used a Durascan model device provided by Struers. To ensure a sufficient distance between the indentation and the edge of the sample, the 50g Knoop hardness method was chosen, in which the large diagonal of the indentation was placed parallel to the plane of the remelted layer. 30 indentations were arranged at the mid-thickness of the remelted layer. Figure 4 An example of hardness measurement is shown. Mark 4 corresponds to the remelted layer, mark 5 corresponds to the Knoop hardness indentation, and mark 6 corresponds to the non-remelted area.

[0178] The hardness was measured according to the Knoop scale with a 50 g load after laser treatment (in the original state) and after additional heat treatment at 400°C for different lengths, allowing in particular to assess the hardenability of the alloy during heat treatment and the influence of a possible HIP treatment on the mechanical properties and electrical conductivity.

[0179] Electrical conductivity measurement

[0180] Based on the fact that the change in electrical conductivity is similar to that of thermal conductivity, electrical conductivity measurements were performed on a 15 mm x 18 mm remelted rectangular surface of each sheet. The linear dependence between thermal conductivity and electrical conductivity has been verified by Hatch in the publication "Aluminum properties and physical metallurgy" ASM Metals Park, OH, 1988, based on the Wiedemann-Franz law. The electrical conductivity measurements were performed in the plane of the larger side of the sheet (the plane parallel to the direction of the laser path) at the center of the remelted surface. The electrical conductivity measurements were performed in the original state (without post-fabrication heat treatment) and after heat treatment at 400°C for different lengths of 1 hour, 4 hours or 7 hours. The average of 5 different measurements was performed under each condition.

[0181] The conductivity measurements were carried out at a temperature of about 20° C., using a measuring instrument of the Foerster Sigmatest 2.069 type at a frequency of 960 kHz. The choice of this frequency allowed limiting the measurement depth of the conductivity to the remelted zone of the sheet.

[0182] The compositions of the experimental aluminum alloys are reported in Table 1 below, in units of weight percent.

[0183] One reference alloy was used: Composition No. 1, which included aluminum, and the following alloying elements: Fe (1.00%) and Zr (1.20%).

[0184] [Table 1]

[0185]

[0186] Table 2 below shows the Knoop hardness (HK0.05) and electrical conductivity values ​​measured for each alloy in the original state (0 hours of heat treatment) after laser reflow.

[0187] [Table 2]

[0188]

[0189] Table 3 below shows the Knoop hardness (HK0.05) and electrical conductivity values ​​measured for each alloy after laser reflow and after annealing at 400° C. for 1 hour after laser reflow.

[0190] [Table 3]

[0191]

[0192]

[0193] Table 4 below shows the Knoop hardness (HK0.05) and electrical conductivity values ​​measured for each alloy after laser reflow and after annealing at 400° C. for 4 hours after laser reflow.

[0194] [Table 4]

[0195]

[0196] Table 5 below shows the Knoop hardness (HK0.05) and electrical conductivity values ​​measured for each alloy after laser reflow and after annealing at 400° C. for 7 hours after laser reflow.

[0197] [Table 5]

[0198]

[0199] The results in Tables 2, 3, 4 and 5 show that for all tested solutions the values ​​of conductivity and hardness are lowest in the original state. The additional heat treatment at 400°C allows to increase both the conductivity and the Knoop hardness (HK0.05) compared to the original state.

[0200] For all tested protocols, the maximum conductivity was obtained after 7 hours at 400°C.

[0201] For all tested solutions, the maximum hardness was obtained after 1 hour to 7 hours of treatment at 400° C. For all tested solutions, the duration for maximizing the hardness showed a range of 0.5 hours to 10 hours.

[0202] Increasing the duration of the heat treatment at 400°C to more than 10 hours allows further improvement of the thermal conductivity, but reduces the hardness.

[0203] Therefore, the final heat treatment can be selected according to the intended application.

[0204] For alloys containing Sc, a heat treatment temperature of 300 to 400°C for 0.5 to 10 hours may be optimal for maximizing hardness. For example, a temperature of 325°C for 4 hours.

[0205] Reference alloy No. 1 achieves the highest electrical conductivity in all tested conditions: in the original state (without any post-fabrication heat treatment) and after heat treatment at 400°C for different durations of 1 hour, 4 hours or 7 hours. For this alloy, the best Knoop hardness (HK0.05) / conductivity (MS / m) compromise is obtained after post-fabrication heat treatment at 400°C for 4 hours, when the hardness value is 113.32HK0.05 and the conductivity is 28.64MS / m. This alloy provides an excellent candidate for applications requiring high thermal or electrical conductivity, such as heat exchangers, radiators, electronic boxes, radio frequency antennas, etc. However, the maximum hardness (113.32HK0.05) that can be achieved by this alloy is still insufficient for some applications that do not require specific properties in terms of electrical conductivity but require high mechanical strength, such as structural parts, hydraulic blocks, etc.

[0206] Tables 4 and 5 show that all alloys of the present invention can provide higher Knoop hardness (HK0.05) than reference alloy No. 1 after heat treatment, wherein alloy No. 4 has a maximum hardness of 149.69 HK0.05 after heat treatment at 400°C for 4 hours after manufacture.

[0207] All alloys of the present invention can achieve good part processing performance in the LPBF process, as well as excellent mechanical properties of the parts in use. Good part processing performance in the LPBF process can be achieved by combining a sufficiently low hardness level in the original state of manufacture (the Knoop hardness HK0.05 in the original state of manufacture is lower than 140, preferably lower than 130, preferably lower than 120) and a sufficiently high thermal conductivity or electrical conductivity (the electrical conductivity in the original state of manufacture is higher than 6MS / m, preferably higher than 7MS / m, preferably higher than 8MS / m). This combination of hardness and electrical conductivity can limit the residual stress level of the parts in the original state of manufacture, significantly limit the risk of cracking, delamination or deformation, and thus significantly improve the part processing performance in the LPBF process. The excellent mechanical properties of the parts in use can be achieved by maximizing the hardness of the parts after post-manufacturing heat treatment (for example, after heat treatment at 400°C for 4 hours, the Knoop hardness HK0.05 is higher than 70, preferably higher than 80, preferably higher than 90, preferably higher than 100, preferably higher than 114).

[0208] Table 1 shows that, unlike reference alloy No. 1, the total content of added elements in all alloys of the present invention is greater than 3%.

Claims

1. A method for manufacturing a part (20), the method comprising forming successive metal layers (201 ... 20 n ), each layer being formed by depositing a filler metal (15, 25) to which energy is input so as to melt and to form the layer when solidified, the method being characterized in that the filler metal (15, 25) is an aluminum alloy containing the following alloying elements (in weight %): - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%; - at least one alloying element selected from Cr, V, Ti and Mn, the mass fraction of V, Ti and Mn being greater than 0.50% each and in total, preferably greater than 0.50 to 6.00%, preferably 1.00 to 5.00%, more preferably 1.00 to 4.00%, even more preferably 1.00 to 3.00%; the mass fraction of Cr being greater than 0.50 to 3.00%; - optionally at least one selected from Co, La, Ce, rare earth metal mixtures, W, Ta, Alloying elements of Mo and Nb, whose mass fractions are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and whose mass fractions are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and whose mass fractions in total are less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%; - Fe, whose mass fraction is 0.10 to 2.50%, preferably 0.15 to 2.50%, preferably 0.20 to 2.50%, more preferably 0.30 to 2.50%, even more preferably 0.50 to 2.50%, even more preferably 0.75 to 2.25%; - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%; - optionally Si, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; preferably less than 0.30%, preferably less than 0.20%; - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%; - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%; - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%; - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%; - optionally at least one element selected from the group consisting of Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, each with a mass fraction less than or equal to 1.00%, Preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, Preferably less than or equal to 0.30%; - Impurities: <0.05% each and <0.15% in total; The rest is aluminum.

2. The method according to claim 1, characterized in that The aluminum alloy contains at least one alloying element selected from the group consisting of Co, La, Ce, mischmetal, W, Ta, Mo and Nb.

3. A method according to any one of the preceding claims, wherein the mass fraction of aluminium is less than 97%.

4. The method according to any one of the preceding claims, wherein the part (20) has: - in the original state of manufacture, the electrical conductivity is higher than 6MS / m, preferably higher than 7MS / m, preferably higher than 8MS / m; and - In the original state of manufacture, the Knoop hardness HK0.05 is lower than 140, preferably lower than 130, Preferably less than 120; and After post-treatment at 400° C. for 4 hours, the Knoop hardness HK0.05 is higher than 70, preferably higher than 80, preferably higher than 90, preferably higher than 100, preferably higher than 114.

5. The method according to any one of the preceding claims, comprising forming a layer (201 ... 20 n ), i.e. after the final part is formed, a post-manufacturing heat treatment is applied, preferably tempering or annealing.

6. A method according to any one of the preceding claims, wherein no solution heat treatment and / or quenching is performed after forming the layer, ie after forming the final part, or after post-manufacturing heat treatment.

7. A method according to any one of the preceding claims, characterised in that This is carried out at a preheating temperature T of up to 500°C.

8. A method according to any one of the preceding claims, wherein the filler metal is in the form of a powder (15) which is exposed to a light beam (12) or a charged particle beam, causing local melting and then solidification, thereby forming a solid layer (201 ... 20 n ).

9. A method according to any one of claims 1 to 7, wherein the filler metal originates from a filler wire (25) which is exposed to a heat source (22) causing local melting and then solidification to form a solid layer (201 ... 20 n ).

10. Metal part obtained by the method object according to any of the preceding claims.

11. A powder intended for use as a filler material in an additive manufacturing process, characterized in that It consists of an aluminum alloy containing the following alloying elements (in wt. %): - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%; - at least one alloying element selected from Cr, V, Ti and Mn, the mass fraction of V, Ti and Mn being greater than 0.50% each and in total, preferably greater than 0.50 to 6.00%, preferably 1.00 to 5.00%, more preferably 1.00 to 4.00%, even more preferably 1.00 to 3.00%; the mass fraction of Cr being greater than 0.50 to 3.00%; - optionally at least one selected from Co, La, Ce, rare earth metal mixtures, W, Ta, Alloying elements of Mo and Nb, whose mass fractions are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and whose mass fractions are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and whose mass fractions in total are less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%; - Fe, whose mass fraction is 0.10 to 2.50%, preferably 0.15 to 2.50%, preferably 0.20 to 2.50%, more preferably 0.30 to 2.50%, even more preferably 0.50 to 2.50%, even more preferably 0.75 to 2.25%; - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%; - optionally Si, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; preferably less than 0.30%, preferably less than 0.20%; - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%; - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%; - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%; - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%; - optionally at least one element selected from the group consisting of Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, each with a mass fraction less than or equal to 1.00%, Preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, Preferably less than or equal to 0.30%; - Impurities: <0.05% each and <0.15% in total; The rest is aluminum.

12. Use of the powder according to claim 11 for a manufacturing method, wherein the manufacturing method is selected from: electron beam melting, cold spray consolidation, laser melting deposition, additive friction stirring, field assisted sintering or inertia rotation friction welding, preferably cold spray consolidation.

Citation Information

Patent Citations

  • Method of manufacturing aluminum alloy articles

    US20170016096A1

  • Methods for producing forged products and other worked products

    WO2015006447A1